The Role of Emotion Regulation in Increasing Resilience to Stress and Life Pressure - Mumtazah, Laura (Jujurnal Publisher, 2024)
Emotional regulation plays a crucial role in enhancing resilience to stress and life pressures. This study employs a qualitative method through a literature review (library research) to explore the relationship between emotional regulation and resilience. By analyzing various scholarly sources, this research examines how effective emotional regulation strategies contribute to individuals' ability to adapt to adversities and maintain psychological well-being. The findings indicate that emotional regulation functions as a protective factor, enabling individuals to manage negative emotions, reframe stressful situations, and develop coping mechanisms that foster resilience. Cognitive reappraisal, emotional acceptance, and mindfulness are among the key strategies that strengthen resilience by promoting adaptive emotional responses. Furthermore, the study highlights that individuals with higher emotional regulation skills exhibit greater psychological flexibility, which helps mitigate the adverse effects of stress. The role of emotional intelligence in facilitating emotional regulation is also emphasized, as it enhances self-awareness, impulse control, and interpersonal effectiveness. This research underscores the importance of integrating emotional regulation training into mental health interventions and educational settings to improve individuals' resilience against life’s challenges. Future studies are recommended to explore the long-term impact of emotional regulation on resilience in diverse populations and cultural contexts. Overall, understanding and cultivating emotional regulation skills are essential for fostering resilience, reducing stress, and enhancing overall well-being.